KONTRIBUSI PEMIKIRAN INKLUSIF NURCHOLISH MADJID TERHADAP KEBERAGAMAAN AGAMA DI INDONESIA - M. Anang Sholikhudin; Lailatul Lutfiyah; M. Afifuddin (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
Nurcholish Madjid’s inclusive thought plays a crucial role in shaping a modern religious life that is open, tolerant, and appreciative of diversity. Through his ideas on substantial and contextual Islam, Madjid emphasizes that true faith should not be confined to exclusive symbols but manifested in universal human values. This study aims to analyze the relevance of Nurcholish Madjid’s inclusive ideas to modern religious life, particularly in strengthening interfaith tolerance and developing a moderate Islamic education. This research employs a library research method with a descriptive-analytical approach to Madjid’s works and ideas. The findings indicate that Madjid’s inclusive values—such as freedom of thought, respect for diversity, and humanistic principles—remain highly relevant in building a peaceful and harmonious religious society in the modern era.